On Corporate Borrowing, Credit Spreads and Economic Activity in Emerging Economies: An Empirical Investigation - Julián Caballero; Andrés Fernández; Jongho Park (Inter-American Development Bank (IDB), 2016)
This paper studies the influence of external financial factors on economic activity in emerging economies (EMEs) motivated by a considerable increase in foreign financing by the corporate sector in EMEs since the early 2000s, mainly in the form of bond issuance. A quarterly external financial indicator for several EMEs is built using bond-level data on spreads of corporate bonds issued in foreign capital markets, and its relationship with economic activity is examined. Results show that the indicator has considerable predictive power on future economic activity. Furthermore, an identified adverse shock to the financial indicator generates a large and protracted fall in real output growth, and about a third of its forecast error variance is associated with this shock. These findings are robust to controlling for possible spillovers from sovereign to corporate risk, among other considerations.
hdl:11319/7793
Keywords: E32; E37; F34; F37; G15; 330; Corporate bonds; Options adjusted spread; Economic activity; Emerging economies